Matric suction effect on distribution of stresses caused by vehicle wheels on a bare silty sand - Torrico Bravo Juan Alfredo; Miranda Salvador; Cornellis Wim; Rojas Juan Carlos; Bezuijen Adam; Di Emidio Gemmina (MATEC Web of Conferences, 2021)
-Soil compaction in cropping systems, caused by the external pressure of machinery, creates impermeable layers that restrict water and nutrient cycles reducing agricultural production. To evaluate the matric suction effects on distribution with depth of stresses in a soil, caused by the use of agricultural machinery, Jet Fill tensiometers were installed at two different depths (i.e. 0.15 m, 0.30 m) in a soil profile constituted by silty sand with gravel (SM); to register the increments on subsoil vertical stresses, two miniaturized load cells (i.e. 16. 5 mm in diameter) were installed in a horizontal position under the centre line of the vehicle wheels’ path, at approximately 0.15 m and 0.30 m depth. Care was taken to calibrate the load cells in field conditions. A vehicle was made to pass over the soil surface, at a speed less than 5 km/h; the tyre inflation pressure applied on wheel was 380 kPa. Response of load cells to vehicle loading was evaluated at different average matric suction measured on soil profile. Finally, measured stresses have been compared with values obtained by applying well-known elastic theoretical methods used to assess stresses applied by tyres on bare soils. The corresponding results show that the increment of vertical stresses decreases as matric suction increases, and a good correlation between measurements and simulations of the increment on subsoil vertical stress.